Increased elongase and desaturase gene expression with stearidonic acid enriched diet does not enhance long-chain (n-3) content of seawater Atlantic salmon (Salmo salar L) 1-3 - Miller, MR; Bridle, AR; Nichols, PD; Carter, CG (The Journal of Nutrition, 2008)
Atlantic salmon (Salmo salar L.) can produce (n-3) long-chain (LC)-PUFA when fed biosynthetic precursors. This has potential for developing sustainable aquafeeds. Echium oil (EO) is rich in stearidonic acid [SDA; 18:4(n-3)] and bypasses the initial D6 desaturase (FAD6) step in the (n-3) LC-PUFA biosynthetic pathway. EO was fed to seawater Atlantic salmon for 12 wk and compared with fish fed a diet containing canola oil (CO), a source of a-linolenic acid [ALA; 18:3(n-3)] or fish oil (FO) that provides (n-3) LC-PUFA. Fatty acid (FA) composition of liver, white muscle, and whole fish was measured to show whether dietary precursors were endogenously biosynthesized to LC-PUFA. Gene expression of liver FA elongase and FAD5 was upregulated in EO fish compared with FO fish. Furthermore, dietary precursors affected the FA concentrations of direct biosynthetic products in all tissues. The increased gene expression in the EO fish was reflected by an increased FA concentration of eicosapentaenoic acid [20:5(n-3)] in the liver compared with the CO fish. However, the high concentrations of (n-3) LC-PUFA found in seawater Atlantic salmon fed diets rich in FO were not attained via biosynthesis from precursors (ALA or SDA) in diets. J. Nutr. 138: 2179–2185, 2008.